We often need to convert inverse of cot to either inverse of cos, sin, tan, sec, cosec x .In this post we will see how to convert cot inverse to sin, cos, tan, sec, cosec x inverse

## Inverse of cot to inverse of sin

**Case 1**

$cot^{-1} x$ and x > 0

Now we can write as

$\theta=cot^{-1} x$

$cot \theta =x$

Now we know that here $\theta \in [0,\pi/2]$, so it is an acute angle

Now it can be written as

$cot \theta =\frac {x}{1} = \frac {base}{perp}$

In Right angle triangle

Now then hyp becomes

$\text{hyp} = \sqrt { 1 +x^2}$

So , $sin \theta = \frac {perp}{hyp} = \frac {1}{\sqrt { 1 +x^2}}$

or

$\theta= sin^{-1} \frac {1}{\sqrt { 1 +x^2}}$

or $cot^{-1} x = sin ^{-1} \frac {1}{\sqrt { 1 +x^2}}$

**Case **2

$cot^{-1} x$ and x < 0

So value of the function will be in the range $[\pi/2 , \pi)$

Now we know from the property that

$cot^{-1} (-x)= \pi – cot^{-1} (x)$

This can be written as

$cot^{-1} x = \pi – cot^{-1} |x| =\pi – sin ^{-1} \frac {1}{\sqrt { 1 +x^2}}$

This makes sense also as Range of the cot and sin function differ. We can convert with out worrying about the sign in $[0, \pi/2]$ as it is common

Thus ,we have different formula depending on the values of x

## Inverse of cot to inverse of cos

**Case 1**

$cot^{-1} x$ and x > 0

from the above, we can write that

$cos \theta = \frac {base}{hyp} = \frac {x}{\sqrt {1+x^2}}$

or

$cot^{-1} x = cos^{-1} \frac {x}{\sqrt { 1 +x^2}}$

**Case **2

$cot^{-1} x$ and x < 0

So value of the function will be in the range $[\pi/2 , \pi)$

Now we know from the property that

$cot^{-1} (-x)= \pi – cot^{-1} (x)$

$cot^{-1} x = \pi – cot^{-1} |x| = \pi – cos^{-1} \frac {|x|}{\sqrt { 1 +|x|^2}}= cos^{-1} \frac {x}{\sqrt { 1 +x^2}}$

So we have same formula for any values of x

$cot^{-1} x = cos^{-1} \frac {x}{\sqrt { 1 +x^2}}$

## Inverse of cot to inverse of tan

**Case 1**

$cot^{-1} x$ and x > 0

from the above, we can write that

$tan \theta = \frac {perp}{base} = \frac {1}{x}$

or

$cot^{-1} x = tan^{-1} \frac {1}{x}$

**Case **2

$cot^{-1} x$ and x < 0

Now we know from the property that

$cot^{-1} (-x)= \pi – cot^{-1} (x)$

$cot^{-1} x = \pi – cot^{-1} |x| = \pi – tan^{-1} \frac {1}{|x|}= \pi + tan^{-1} \frac {1}{x}$

This makes sense also as Range of the cot and tan function differ. We can convert with out worrying about the sign in $[0, \pi/2]$ as it is common

Thus ,we have different formula depending on the values of x

## Inverse of cot to inverse of sec

**Case 1**

$cot^{-1} x$ and x > 0

from the above, we can write that

$sec \theta = \frac {hyp}{base} = \frac {\sqrt {1+x^2}}{x}$

or

$cot^{-1} x = sec^{-1} \frac {\sqrt {1+x^2}}{x}$

**Case **2

$cot^{-1} x$ and x < 0

So value of the function will be in the range $[\pi/2 , \pi)$

Now we know from the property that

$cot^{-1} (-x)= \pi – cot^{-1} (x)$

$cot^{-1} x = \pi – cot^{-1} |x| = \pi – sec^{-1} \frac {\sqrt {1+x^2}}{|x|}= sec^{-1} \frac {\sqrt {1+x^2}}{x}$

So we have same formula for any values of x

$cot^{-1} x = sec^{-1} \frac {\sqrt {1+x^2}}{x}$

## Inverse of cot to inverse of cosec

**Case 1**

$cot^{-1} x$ and x > 0

from the above, we can write that

$sec \theta = \frac {hyp}{perp} =\sqrt {1+x^2}$

or

$cot^{-1} x = cosec^{-1} \sqrt {1+x^2}$

**Case **2

$cot^{-1} x$ and x < 0

So value of the function will be in the range $[\pi/2 , \pi)$

Now we know from the property that

$cot^{-1} (-x)= \pi – cot^{-1} (x)$

$cot^{-1} x = \pi – cot^{-1} |x| = \pi – cosec^{-1} \sqrt {1+x^2}$

I hope you like this article on how to convert cot inverse to sin, cos, tan, sec, cosec x inverse

**Related Articles**

how to convert cosec inverse to sin, cos, tan, sec x, cot inverse

how to convert sec inverse to sin, cos, tan, cosec x, cot inverse

how to convert sin inverse to cos, tan, sec, cosec x, cot inverse

how to convert cos inverse to sin, tan, cosec x, cot inverse

how to convert tan inverse to sin, cos, sec, cosec x, cot inverse